PENERAPAN STRATEGI GENIUS LEARNING DENGAN OPERAN KERTAS IDE - iltavia iltavia; Pristy Yuliani (Jurnal Ipteks Terapan, 2019)
The purpose of this study was to determine the results of cognitive, affective, and psychomotor learning of students with the application of Genius Learning Strategy with Idea Paper Operations. The type of research is experimental research. The research design that will be used is Randomized Control Group Design. Where for the experimental class is the class that feels with the Genius Learning strategy with Operan Kertas Ide Technique, while the control class is a powerless class with the Genius Learning strategy with Operan Kertas Ide Technique. The results of research on cognitive learning outcomes that implemented the Genius Learning strategy with Operan Kertas Ide is better than the result of learning mathematics students without implementing Genius Learning strategy with Operan Kertas Ide on the material set in class VII SMP Padangpanjang. The learning outcomes of students in the affective and psychomotor domains obtained through the observation sheet increased in each meeting during the learning process that implemented the strategy of Genius Learning with Idea Paper Operations in the class VII SMP Padangpanjang. So, it can be concluded that Genius Learning Strategy with Idea Paper Idea can improve students' cognitive, affective and psychomotor learning outcomes.